Cassava program - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
The strategies and projections of CIAT's cassava program for the period 1986-90 are described and analyzed in detail. Background information is given on the crop including its characteristics and end uses (fresh cassava for foodstuffs, both traditional and innovative dry cassava products). A comprehensive review of the program since its initiation is made and major accomplishments are summarized. The production and potential demand for cassava are analyzed by regions: Latin America, southern and eastern Asia, and sub-Saharan Africa. The cassava program has designed global strategies to achieve its objectives; the following basic activities to fulfill its global mandate are outlined: the role of cassava in the economies of the developing world; basic understanding of the crop; germplasm development; production systems; utilization technologies for fresh cassava, CF, and animal feed; and documentation and information. CIAT's regional responsibilities in Latin America and the Caribbean, sub-Saharan Africa, and southern and eastern Asia are discussed. Staffing projections for the period are presented. (CIAT)